Does the EU judicial review mechanism provide a complete system of remedies and procedures for private individuals? - Lopez, Gizem Köstem Vinuales (My University, 2019)
Bireylerin etkin hukuki korunması hukukun üstünlüğünü kabul eden modern hukuk sistemlerinde önemli bir kavram olarak kabul edilmektedir. Bu sebeple, bu terimin AB hukuk düzeninde uzun zamandan beri tartışma konusu olması şaşırtıcı değildir. Temel hakların korunması, hukukun üstünlüğü ve doğru işleyen bir hukuki denetim mekanizmasının varlığı ile yakından bağlantılı olan bireylere hukuki korunma sağlanması prensibi eksiksiz bir usul hukuki sisteminin varlığı için vazgeçilmez bir unsurdur.ABAD’nın iptal davası konusundaki katı yorumlarına rağmen, akademik tartışmalar, Hukuk Sözcüsü Jacobs’un meşhur mütaalası, ve özellikle Lizbon Antlaşması’nda madde metninde yapılan değişiklikler dava ehliyeti konusundaki şartları yumuşatmaya katkıda bulunmuştur. ABAD içtihatlarında istikrarlı bir şekilde, AB hukuk sisteminin bireyler için tam ve eksiksiz bir usul hukuku kurallar bütünü sağladığını belirtse de, Lizbon değişiklikleriyle dahi, bu modern hukuk sisteminin bireylere sağlaması beklenen hukuki korumayı sağladığını söylemek mümkün değildir. Bireylere tanınan diğer dava çeşitleri karakteristik özelliklerinden ötürü, bireylere hukuki korunma sağlanması konusunda etkin alternatifler olarak değerlendirilememektedir. Her ne kadar, AB’de bireylerin etkin korunması konusunda son birkaç on yılda gerçekleşen gelişmelerin hafife alınması mümkün olmasa da bu kendine özgü, ve gelişmiş hukuk sisteminin bireylere daha bütün ve eksiksiz bir hukuki koruma sağlaması için köklü değişikliklerin yapılması zamanı gelmiştir.

The effective judicial protection of individuals has been an important notion in the modern legal systems that are ruled by law. It is not surprising that this concept has long been discussed in the EU legal order. The presence of a complete system of remedies and procedures is a must for a legal system to provide an effective judicial system to individuals which is closely linked to the protection of fundamental rights, rule of law, and a properly functioning judicial review system. Despite the strict interpretation of the CJEU on the action for annulment, the academic debates, the famous opinion of the AG Jacobs and especially the amendments that have taken place in the article with the Lisbon Treaty have contributed to the relaxation of the locus standi criteria. Although the CJEU had consistenly stated that the EU legal order had a complete system of remedies for individuals in its case-law, even with the Lisbon amendments it is difficult to conclude that this modern legal system provides the judicial protection that it should to individuals. The other procedures that are provided for the individuals cannot be considered to be as effective alternatives for the protection of individuals due to the characteristic of these procedures. The progress that has taken place in the field of judicial protection in the EU within the last decades cannot be underestimated, however, it is time for drastic changes in order to provide a more complete judicial protection sytem to individuals in this sui generis and developed legal order. The effective judicial protection of individuals has been an important notion in the modern legal systems that are ruled by law. It is not surprising that this concept has long been discussed in the EU legal order. The presence of a complete system of remedies and procedures is a must for a legal system to provide an effective judicial system to individuals which is closely linked to the protection of fundamental rights, rule of law, and a properly functioning judicial review system. Despite the strict interpretation of the CJEU on the action for annulment, the academic debates, the famous opinion of the AG Jacobs and especially the amendments that have taken place in the article with the Lisbon Treaty have contributed to the relaxation of the locus standi criteria. Although the CJEU had consistenly stated that the EU legal order had a complete system of remedies for individuals in its case-law, even with the Lisbon amendments it is difficult to conclude that this modern legal system provides the judicial protection that it should to individuals. The other procedures that are provided for the individuals cannot be considered to be as effective alternatives for the protection of individuals due to the characteristic of these procedures. The progress that has taken place in the field of judicial protection in the EU within the last decades cannot be underestimated, however, it is time for drastic changes in order to provide a more complete judicial protection sytem to individuals in this sui generis and developed legal order.
Keywords: AB hukuku Private parties; Avrupa Birliği; effective judicial protection; etkin hukuki koruma; EU law; European Union; gerçek ve tüzel kişiler; Hukuk; Law